الدراسة الأدبية للخطابة النبوية: LITERARY STUDY OF THE PROPHETIC RHETORIC (Zia e Tahqeeq, 2025)
The Prophet Muhammad, may Allah bless him and his family, is known for his rhetoric used in his sermons. Some of his sermons were short while the others are extended. The Prophet's sermons are consisted upon various topics in which he exhorts people to think about the universe, it’s Creator. He also addresses their social and moral problems and guides the audience regarding intellectual, theological and ideological discussions in a simplistic style. The common denominator that distinguishes these short and long speeches is the power of their influence in the hearts of listeners. The speeches of the Prophet Muhammad - may Allah bless him- are unique due to the usage of excellent proper usage of literary words. This paper highlights the characteristics of his speeches and literary value of his sermons in Arabic Language.